Malawi Farm Input Subsidy Programme - impact on income of smallholder farmers - Musonzo, Charity Priscilla (Research of GSB, 2018)
Agriculture is the single most important sector in Malawi due to its contribution to the economy ranging from employment creation, contribution to GDP growth to source of foreign exchange earnings. These significant contributions have necessitated the Government of Malawi to develop strategies and policies such as the Farm Input Subsidy Programme (FISP), whose main aim is to increase household incomes and reduce food insecurity and ultimately reduce poverty. It is nine years since the introduction of FISP but its results remain mixed. Using the 2009/10 Integrated Household Survey Phase 3 (IHS3) dataset, a logistic regression in a multivariate data analysis approach was used to investigate the impact of FISP on income levels and food security of rural smallholder farmers in Malawi. The analysis showed that about 82 percent of smallholder farmers live in rural areas, about 75 percent of them were males, 71 percent were married, 70 percent did not go to school and 69 percent benefited from FISP. In farming, 68 percent of these smallholder farmers had less than 1 hectare of farms, 70 percent of them had labour force of less than 5 people, 51 percent of them harvest less than 5 bags of 50kgs of maize of which 92 percent sell most of their harvested maize and 89 percent of them receive less than MK5, 000 from sales. In addition, about 99 percent of these smallholder farmers were food insecure as they save less than 1 bag of 50kgs after harvest. Only 1 percent of these smallholder farmers receive remittances and 21 percent had other income generating activities (IGAs). Demographic and socio-economic factors have no impact on these farmers capability to increase income levels and enhance their food security. There is also no statistically significant difference between FISP beneficiaries and non-beneficiaries in terms of capabilities of increasing incomes and enhancing food security. It is, therefore, concluded that FISP had no significant impact on the abilities of these smallholder farmers to increase their incomes and enhancing their food security. Hence, FISP did not prove to be the best food security and poverty alleviation tool in Malawi.